Catalytic activity of CuFe2O4 spinel oxide for liquid-phase oxidation of cinnamyl alcohol - Dange, Rutvija M.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
CuFe2O4 spinel oxide catalyst was synthesized by sol-gel and co-precipitation methods for liquid phase oxidation of Cinnamyl alcohol (CnOH) to Cinnamaldehydes (CnHO) using tert-Butyl hydroperoxide (TBHP) as oxidising agent. Spinel oxide catalyst was characterized by different techniques such as X-ray diffraction (XRD), N-2 adsorption-desorption, BET surface area, and X-ray photoelectron spectroscopy (XPS) to understand the structural, physical properties and oxidation state of the catalyst. The result shows that catalyst prepared by sol-gel method was found higher surface area and smaller crystalline size than co-precipitation method. XPS data confirm the formation of Cu2+ in the spinel which helps to improve the catalytic activity of oxidation. This reaction follows radical mechanism, and exhibited 76.7 % of CnOH conversion and 68.4 % of CnHO, and 24.8 % benzaldehyde (benzald) selectivity using TBHP at 60 degrees C. Kinetic data reveal that 41.2 kJ/mol of activation energy for the reaction. The higher activity of spinel oxide catalyst could be due synergetic effect of spinel (88 %) and oxides (12 %) formed in the catalyst, which helps to provide the oxygen during reaction. The contribution of Cu2+ is higher in sol-gel than co-precipitation, which may provide the better reactivity of catalyst. This work helps to select the effective and cost-effective catalyst for the oxidation of CnOH.
Keywords: Catalysts; Cinnamaldehyde; Cinnamyl Alcohol; Cupper; iron; oxide; spinel

Methanol-to-light olefins reaction using Zn-Ag modified SSZ-13 catalyst - Dange, Rutvija M.; Gawali, Chirag B.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
The 2 wt.% of Zn and Ag (Zn1-x-Ag-x; x=0.2, 0.4, 0.6 %) modified SSZ-13 (SZ-13) zeolite was prepared by wet-impregnation method, and its catalytic activity was demonstrated for methanol-to-olefin (MTO). The Zn-0.6-Ag-0.4/SZ-13 catalyst exhibited high catalytic activity due to change in properties of catalyst. The Zn particles were highly dispersed inside the SZ-13; while Ag particles were dispersed on the surface of SZ-13, confirmed by HRTEM and surface area. The small % of Ag over SZ-13 promotes ethylene production via aromatization of reaction, and highly dispersed Zn on SZ-13 help to produce stable ethylene and propylene. The Zn-0.6-Ag-0.4/SZ-13 catalyst showed (similar to 10 %) higher light olefin (87 %) selectivity than parent SZ-13 as well as mono metal incorporated SZ-13. The higher catalytic activity was attributed due to effect of both metals (Zn and Ag), where Ag promotes partial aromatization on the surface, and Zn increases the Lewis acidity in the zeolite pore. This catalyst can help to improve the selectivity of light olefin using MTO reaction.
Keywords: Ethylene; Methanol-to-Olef; Propyl; Silver; SSZ; zinc